2021
DOI: 10.1136/bmjopen-2020-046112
|View full text |Cite
|
Sign up to set email alerts
|

Are the rights of people with disabilities included in international guidance on WASH during the COVID-19 pandemic? Content analysis using EquiFrame

Abstract: PurposePeople with disabilities are at increased risk from COVID-19. Access to water, sanitation and hygiene (WASH) services and facilities is a fundamental right for all, and is vital in stopping the transmission of COVID-19. However, people with disabilities often face difficulties accessing WASH. Various international organisations have published guidance and recommendations on WASH service provision during the COVID-19 pandemic, and this must include information of relevance to people with disabilities. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…A consistent finding across studies which explore inclusive WASH is that caregivers are not recognized for the critical support roles they often play in supporting people with disabilities and older adults with WASH and maintaining personal hygiene (21,26,30,(49)(50)(51). Our study found a greater emphasis on caregivers (Family resource) than in other studies (37,39,48). As noted above, though this indicates an awareness of caregivers' importance, this attention did not translate into clearly articulated actions for this group, meaning they were also unlikely to benefit extensively from these efforts.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A consistent finding across studies which explore inclusive WASH is that caregivers are not recognized for the critical support roles they often play in supporting people with disabilities and older adults with WASH and maintaining personal hygiene (21,26,30,(49)(50)(51). Our study found a greater emphasis on caregivers (Family resource) than in other studies (37,39,48). As noted above, though this indicates an awareness of caregivers' importance, this attention did not translate into clearly articulated actions for this group, meaning they were also unlikely to benefit extensively from these efforts.…”
Section: Discussionsupporting
confidence: 81%
“…However, the total number of references made to individual core concepts was limited, particularly about aging, which was woefully low. Across this and other similar studies, Individualized services and Access are referenced consistently highly, whilst Participation, Capability based services, and Accountability receive little attention (37,39,48). Some may think this unsurprising because many governments, organizations, and institutions aim to increase access to WASH services, particularly in an emergency setting.…”
Section: Discussionmentioning
confidence: 70%
“…Inadequate effective and meaningful participation of people with disabilities in WASH programs, from design to evaluation, has been widely documented in development settings (Groce et al, 2011;UN Water, 2015;Scherer et al, 2021b;Wilbur et al, 2021b). Evidence also exists from humanitarian settings, including two papers which explore the extent to which the rights of persons with disabilities are included in international guidance on WASH responses to prevent the transmission of COVID-19 (Scherer et al, 2021a) and interventions (Wilbur, in press). Both found that participation was referenced significantly less than ensuring access to WASH infrastructure in guidance documents (Scherer et al, 2021a) and interventions (Wilbur, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also exists from humanitarian settings, including two papers which explore the extent to which the rights of persons with disabilities are included in international guidance on WASH responses to prevent the transmission of COVID-19 (Scherer et al, 2021a) and interventions (Wilbur, in press). Both found that participation was referenced significantly less than ensuring access to WASH infrastructure in guidance documents (Scherer et al, 2021a) and interventions (Wilbur, in press). These patterns are apparent in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation